2018
DOI: 10.1590/0103-6440201802027
|View full text |Cite
|
Sign up to set email alerts
|

Photoanthropometry of the Face in the Young White Brazilian Population

Abstract: The aim of the present study is to describe the simplified facial pattern of young Brazilian men and women using the facial index (FI), upper face index (UFI), and nasal index (NI) in indirect anthropometric measurements applied to frontal photographic images. The images were obtained from 660 adult white men and 689 adult white women aged 30 years ± 6 months, and classified according to regions of birth, as follows: south (S), southeast (SE), midwest (MW), northeast (NE), and north (N). The nasion, zygion, gn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
(29 reference statements)
0
4
0
2
Order By: Relevance
“…There exist numerous 2D face databases for various purposes. Facial anthropometry researchers build 2D face databases in the healthcare field [1], [2], [8], [9], [17] to evaluate facial feature differences between populations. On the other hand, computer vision researchers build 2D face databases [27]- [37], [41] with various poses, illuminations, expressions as well as different accessories (e.g., spectacles, beard, mustache) to evaluate face recognition and detection algorithms.…”
Section: A Two-dimensional Computer Vision Data Setsmentioning
confidence: 99%
See 2 more Smart Citations
“…There exist numerous 2D face databases for various purposes. Facial anthropometry researchers build 2D face databases in the healthcare field [1], [2], [8], [9], [17] to evaluate facial feature differences between populations. On the other hand, computer vision researchers build 2D face databases [27]- [37], [41] with various poses, illuminations, expressions as well as different accessories (e.g., spectacles, beard, mustache) to evaluate face recognition and detection algorithms.…”
Section: A Two-dimensional Computer Vision Data Setsmentioning
confidence: 99%
“…These landmarks are used when calculating measurements using traditional featurebased approaches (linear and vertical) that are handcrafted by researchers and have successfully been used in ethnicity and sex estimation studies. Linear measurement studies [1], [2], [2]- [4] compute horizontal and/or vertical distances between identified anthropometric landmarks using Euclidean distances. Whereas, angular measurement studies [5]- [7] generate facial angles from anthropometric landmarks instead.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the world wars of the 20th century, the presence of immigrants from Japan, Eastern Europe, the Middle East, Italy and Germany became important [14]. Their distribution was not even among the regions and, therefore, it is clear that each segment of Brazil has its own physical features that represent the dominant population groups, with different characteristics [15]. The increasing and continuous lack of ancestral uniformity, as it is observed in Brazil, raises the question whether or not the use of a single STT chart is appropriate for the estimation of facial morphology [16].…”
Section: Introductionmentioning
confidence: 99%
“…O território brasileiro com sua extensão de proporções continentais, é formado por regiões geográficas (norte, nordeste, sudeste, sul e centro-oeste) com características ambientais e de formação populacional tão distintas que cada região poderia representar uma população com características distintas(14). A crescente e contínua miscigenação da população brasileira resultou numa sobreposição importante de variadas características morfológicas cranianas.…”
unclassified